Decentralization of the firm: theory and evidence - Christie, Andrew A; Joye, Marc P; Watts, Ross L (Journal of Corporate Finance, 2003)
Value maximization requires either that knowledge is transferred to those with the right to make decisions, or that decision rights are transferred to those who have the knowledge. A tradeoff of knowledge transfer costs and control costs is required. Characteristics of firms' investment opportunity sets (IOSs) that affect knowledge transfer costs and control costs are identified. Testable predictions about the relations between these characteristics and firms' decentralization decisions are developed and tested. The evidence presented is consistent with our predictions and is robust to different ways of measuring variables.